Impacts of laparoscopic hysterectomy on functions of coagulation and fibrinolysis system. Issue 4 (June 2016) - Zhao, Honghui; Xiao, Wei; Hu, Chunjie; Gao, Xiaoxu; Zhu, Yumei; Yang, Xiaofeng
Abstract : The main objective of the study is to compare the impacts of laparoscopic hysterectomy and total abdominal hysterectomy on the functions of coagulation and fibrinolysis system. Seventy-five patients who had undergone hysterectomy were randomly divided into laparoscopic hysterectomy group ( n  = 38) and total abdominal hysterectomy group ( n  = 37). The prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time (TT), fibrinogen, D-dimer, von Willebrand factor, α-granule membrane protein-140, thrombin-activated fibrinolysis inhibitor (TAFI) and platelet count were detected at preoperative 24 h (N0), postoperative 24 h (N1) and postoperative 48 h (N2). Compared with N0, values of PT, APTT and TT were significantly decreased at N1 in both groups, whereas von Willebrand factor, platelet count and α-granule membrane protein-140 levels at N1 were significantly increased ( P  < 0.05). There was no significant difference between N0 and N2 ( P  > 0.05). Compared with N0, fibrinogen, D-dimer and TAFI levels in both groups were significantly higher at N1 ( P  < 0.05), and there was no significant difference between N0 and N2 ( P  > 0.05). The intergroup comparison showed no significant difference of above indexes between two groups ( P  > 0.05). The univariate analysis showed that TAFI was negatively correlated with TT ( r  = −0.365, P  < 0.01), APTT ( r  = −0.183, P  < 0.05) and PT ( r  = −0.121, P  < 0.05), whereas not correlated with other indicators. Laparoscopic hysterectomy may increase the risk of postoperative venous thrombosis.